Detrimental effect of water submersion of stools on development of Strongyloides stercoralis - Witthaya Anamnart (2018)
Strongyloidiasis is prevalent in Thailand, yet its prevalence in the south is lower than in other parts of the country. This might be due to the long rainy season in the south resulting in stool submersion in water inhibiting worm development. In this study, the effect of water submersion of fecal samples on development of Strongyloides stercoralis was investigated. Ten ml of a 1:5 fecal suspension were placed in 15-ml tubes, 35-mm dishes, and 90-mm dishes producing the depths of 80 mm, 11 mm and 2 mm-suspensions, respectively. The worm development was followed at 1/6, 4, 6, 8, 10, 12, 14, 16, 24, and 36 h, by determining the number of filariform larva (FL) generated from agar-plate cultures (APC). Fecal suspensions kept in tubes and 35-mm dishes showed a decline in FL yield relative to incubation time and reached zero production 14 h after incubation. In contrast, the number of FL generated from the suspension kept in 90-mm dishes remained stable up to 36 h. Cumulatively, all tubes and 35-mm dishes became negative in APC after 14 h while 90-mm dishes remained APC-positive up to 36 h. Adding more water or stool suspension to dishes resulted in a decreased number of FL. Mechanical aeration of the suspensions in tubes restored an almost normal FL yield. It appears that the atmospheric air plays a significant role in growth and development of S. stercoralis in the environment and may be one of factors which contribute to a lower prevalence of human strongyloidiasis in the south of Thailand. © 2013 Anamnart et al.